EXPRESSION OF NATIONAL TRADITIONS AND VALUES IN KARAKALPAK STYLE IN FINE ARTS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article presents the rich historical and cultural heritage of the Karakalpak people, traditions, values and their expression in fine art. The author analyzes the expression of nationality in the art of Karakalpak painting, especially on the example of the famous artist Jollibaya Izentaeva. It reveals how the unique traditions, costumes, decorations, huts and festive rituals of the Karakalpak people are reflected in the work of artists. The role of contemporary artists in expressing nationality and their contribution to highlighting national values in their works is also emphasized. The article also highly appreciates the role and importance of fine arts in promoting nationality.